Variasi Alofon ‘Penghilangan Vokal’ Bahasa Arab Fusha Dalam Dialek Maroko : Analisis Pada Lagu-Lagu Maroko - Lutfiah Rahmah; Risma Pebriyani; Tatang (MUMTAZA Journal of Arabic Teaching, Arabic Linguistic and Literature, 2024)
This study aims to analyze the phonological variation of allophones with the specification of "Vowel Omission" in Moroccan Arabic dialect (Darija) as reflected in Moroccan songs. The songs chosen for this study are the lyrics of "لوجه التاني" by Saad Lamjarred and Zouhair Bahaoui, "بلا بلا" by Nouaman Belaiachi, and "Taragalte" by Oum. Using a qualitative method and content analysis, this research explores how allophones in Darija function differently compared to Modern Standard Arabic (Fusha), with vowel omission being one of the phenomena observed. The study also examines how these phonological variations reflect the social and cultural identity of the speakers. The analysis results show vowel omission in 8 instances in the song "لوجه التاني," 6 instances in the song "Bla-Bla," and 4 instances in the song "Taragalte." Vowel omission and significant vowel changes reflect the flexibility and complexity of Moroccan Arabic, influenced by sociolinguistic factors. This study is expected to contribute to the fields of linguistics and sociolinguistics and enrich the understanding of the interaction between language and culture in Morocco.